Mechanics of flight in ski jumping: aerodynamic stability in pitch - Marques-Bruna, P.; Grimshaw, P. (Sports Technology, 2009)
This study examines aerodynamic stability in pitch in ski jumping. Static stability implies automatic return to trimmed flight after a sudden disturbance and dynamic stability involves gradual damping of oscillatory motion. Both have implications for flight control and safety. A 3-D inertia model of a ski jumper and the Planica K185 jumping hill profile were constructed using computer-aided design. Inertia, jump performance, and aerodynamic efficiency and stability parameters were computed for variations in V-style posture using mathematical modeling. Pitching moment at a 0° angle of attack was positive, and the condition dM/d<0 at equilibrium was satisfied, indicating that the athlete is inherently stable. Enhanced flight posture consists of a ski-opening angle of 30° and a forward-leaning angle of 10°. This is a high-lift configuration with a large static margin that triggers a steep dM/d slope and high oscillatory frequency upon deviations from trimmed attitude. Mechanisms of stability in pitch are proposed, founded upon theoretical aerodynamics.